Analisis Teologis Kasus "Kristen Tanpa Gereja" Berdasarkan Suratan Efesus 4:11-16 - Hengki Irawan Setiabudi; Bindargo (EUNOIA Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
The "churchless Christianity" phenomenon, in which believers maintain faith in Christ while deliberately abandoning connection to a local church, is expanding among Indonesian Millennials and Generation Z and is massively amplified through social media, demanding serious theological examination rather than mere pastoral concern. This study aims to describe the anatomy of the phenomenon, analyze the theological meaning of Ephesians 4:11-16, and evaluate the phenomenon in light of the exegetical findings. The method employed is descriptive qualitative research using library research and exegesis; primary data consist of the Greek text of Nestle-Aland 28th edition, while secondary data comprise accredited journal articles from the last five to ten years and research reports, analyzed through content analysis and reflective-dialogical analysis with source triangulation. The results reveal that the phenomenon constitutes an alternative ecclesiology supported by four actor typologies and four implicit theological claims, while the exegesis yields four propositions that faith growth is christological, corporate, relational-organic, and participatory, so that both meet at four irreconcilable points of tension. This study contributes two new concepts, the privatization of faith and the lost catechesis, which enrich the believing without belonging thesis within a religious society context. The findings imply intergenerational restoration, relational catechesis, and the positioning of spiritual inspiration spaces as bridges back to the church, while opening avenues for further phenomenological research on its actors.